Investigation of surface of photopolymer composite materials for dental application using atomic force microscopy - Zenon, Hotra; Makeev, Valentyn; Mykyevych, Nataliya; Voznyak, Lesya (Видавництво Львівської політехніки, 2012)
Surface microstructures of photopolymer composite materials Filtek Z250, Charisma, Dipol for dental application were investigated by using atomic force microscopy. It was shown that dental inlay Charisma characterized by the smoothest surface and small spread of the height distribution.
Keywords: photopolymer composite material; atomic force microscopy; surface microstructure; dental application